FINANCIAL LEVERAGE STRATEGY TO IMPROVE COMPANY STOCK PERFORMANCE IN INDONESIA - Hayyin Isnaini; Murtanto (ZILLZELL MEDIA PRIMA, 2024)
This research aims to analyze and explore strategies for utilizing financial leverage ratios in improving the performance of company shares traded on the IDX. The sampling technique uses purposive sampling using a cross section data approach of 105 observation sample data from property & real estate sector companies listed on the IDX with the observation period 2020-2023. Meanwhile, the analysis technique uses structural equation modeling. The research results show that the use of financial leverage by companies in the property & real estate sector shows that they are not capable enough to improve the performance of company shares in the secondary market. However, the EVA variable can explain variations in its influence on stock returns indirectly through financial leverage. This indicates that the use of financial leverage is proven to be able to improve current year performance as reflected in the EVA ratio value. Interestingly, company age can also explain variations in its influence on company stock performance. This means that the longer the company is, the greater the opportunity for the company to improve its stock performance.